Improving Listening Through Modern Innovative Strategies (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article highlights some innovative strategies for improving listening skill of English Language of secondary level students. Effective Listening in English language, guiding the students towards effective oral communication, is the problem with all the ESL students at secondary level and as such it creates problem for English language teachers. The objective of the study was to help the English language teachers and students to overcome this problem by showing the results of application of innovative strategies for improving English language listening skill.